Homosexuality and medicine, health and science - Dynes, Wayne R.; Donaldson, Stephen (New York: Garland Publishing, 1992)
"Edited with introductions by Wayne R. Dynes and Stephen Donaldson Fonds Suzan Daniel (FSD)"